Pengembangan biodegradable packing foam dari limbah tongkol jagung dan pelepah pisang sebagai alternatif kemasan berkelanjutan - Novitasari, Zahra Rizki; Maulidya, Nalaina Izzaty; Humairo, Mika Vernicia (Holistik Jurnal Kesehatan, 2025)
Background: Indonesia's waste continues to grow and will reach 70 million tons by 2023. The e-commerce sector is a major contributor to plastic waste, with 96% of its packaging made from plastic, such as foam. Corncob and banana stem waste have the potential to be environmentally friendly alternatives for foam packaging due to their high cellulose content of 26.81% and 83.3%, respectively. Purpose: To develop biodegradable foam packaging made from corncob and banana stem waste as an environmentally friendly packaging alternative. Method: The study used a Research and Development (R&D) model using the 4D approach (define, design, develop, and disseminate). Results: Expert validation demonstrated product feasibility with an average score of 4.5 for durability, elasticity, and density, and a score of 5.0 for physical structure. Secondary packaging validation also demonstrated excellent results, with scores for attractiveness of 4.5; color contrast of 5.0; product protection of 5.0; and sturdiness of 4.5. These results indicate that biodegradable packing foam has the potential to replace conventional foam, offering characteristics that support product protection and are more environmentally friendly. In addition to its functional potential, this product also offers broad market opportunities through strategic partnerships. Conclusion: The use of biodegradable packing foam is expected to reduce plastic waste, support sustainable waste management efforts, and contribute to achieving SDG 12 on responsible consumption and production.   Keywords: Banana Stems; Biodegradable Packing Foam; Corn Cobs; Sustainable Packaging; Waste.   Background: Tumpukan sampah di Indonesia terus meningkat dan mencapai 70 juta ton pada 2023. Sektor e-commerce menjadi penyumbang besar sampah plastik, dengan 96% kemasannya berbahan plastik seperti foam. Limbah tongkol jagung dan pelepah pisang berpotensi menjadi alternatif packing foam ramah lingkungan karena kandungan selulosanya yang tinggi masing-masing 26,81% dan 83,3%. Tujuan: Untuk mengembangkan biodegradable packing foam berbahan dasar limbah tongkol jagung dan pelepah pisang sebagai alternatif kemasan yang ramah lingkungan. Metode: Penelitian dengan model Research and Development (R&D) menggunakan pendekatan 4D (define, design, develop, dan disseminate). Hasil: Validasi ahli menunjukkan kelayakan produk dengan rata-rata skor 4.5 pada aspek daya tahan, elastisitas, dan kepadatan serta skor 5.0 pada struktur fisik. Validasi kemasan sekunder juga menunjukkan hasil sangat baik dengan nilai daya tarik 4.5; kontras warna 5.0; kemampuan melindungi produk 5.0; dan kekokohan 4.5. Hasil ini menunjukkan bahwa biodegradable packing foam berpotensi menggantikan foam konvensional dengan karakteristik yang mendukung perlindungan barang dan lebih ramah lingkungan. Selain potensi fungsionalnya, produk ini juga memiliki peluang pasar yang luas melalui kemitraan strategis. Simpulan: Penerapan penggunaan biodegradable packing foam diharapkan dapat mengurangi sampah plastik, mendukung upaya pengelolaan sampah berkelanjutan, dan berkontribusi terhadap pencapaian SDGs poin 12 tentang konsumsi dan produksi yang bertanggung jawab.   Kata Kunci: Biodegradable Packing Foam; Kemasan Berkelanjutan; Limbah; Pelepah Pisang; Tongkol Jagung.